THE DESIGN OF NORMAL CONCRETE AND BENDRAT FIBRE CONCRETE WITH MAHAKAM SAND AND SPLIT STONES OF KUTAI BARAT - SISHAM, ARNOLD (KURVA S JURNAL MAHASISWA, 2016)
Normal concrete is concrete with content weight of 2200 – 2500 kg/m3 composed of split aggregates. Fibre concrete is a mixture of normal concrete and other fibrous materials, whose fibres measure 5 cm with variation of 5% and 10% of the weight of concrete. This research purpose to investigate the difference between the compressive strength exerted by normal concrete and bendrat fibre concrete and that by coarse aggregate of split from Kutai Barat and sand aggregate from Mahakam.This research utilizes mixed design method (Indonesian National Standard—SNI 03-2847-2002) and is carried out in laboratory with the maximum size of coarse aggregate at 40 mm. The samples collected include normal concrete, fibre concrete of 5% and fibre concrete of 10%, each of which has 30 samples. That said, there are 90 samples in total.Based on the compressive strength test of normal concrete at its 28 days, the value of average compressive strength (f’cr) = 132,25 kg/cm² and the prerequisite compressive strength (f’c) = 115,07 kg/cm², compared to its targeted average compressive strength (f’cr) = 255 kg/cm² and its prerequisite compressive strength (f’c) = 175 kg/cm2. The compressive strength test of 5% fibre concrete at its 28 days shows that the value of average compressive strength (f’cr) = 155,48,25 kg/cm² and the prerequisite compressive strength (f’c) = 134,4 kg/cm², compared to its targeted average compressive strength (f’cr) = 255 kg/cm² and its prerequisite compressive strength (f’c) = 175 kg/cm2. Lastly, the compressive strength test of 10% fibre concrete at its 28 days, the value of the targeted average compressive strength (f’cr) = 159,25 kg/m2 and the prerequisite compressive strength (f’c) = 133,46 kg/cm2, compared to its targeted average compressive strength (f’cr) = 255 kg/cm² and its prerequisite compressive strength (f’c) = 175 kg/cm2.